Pertumbuhan Benih Ikan Betok (Anabas testudineus Bloch) dengan Pemberian Pakan Tambahan Berupa Maggot - Inga Torang (Fakultas Peternakan Universitas Kristen Palangka Raya, 2013)
Feeding by supplement food can promote the growth and survival of climbing perch fry, because climbing perch is omnivorous fish. This study aimed to determine the relative weight of growth of climbing perch fry (Anabas testudineus Bloch) were given maggot as supplement food using peat water media. The results of the study, feeding as much as 3% in a given day morning and 1% pelleted feed given during the day mixed pellet feed maggot 1% and given the afternoon to feed the maggot 1% growth of 35.6% relative weight and condition factor of 2:21 with a feed conversion rate of 3.40. Maggot is one outcome of the bioconversion of organic materials into organic vegetable animal with a relatively high protein content by fermentation of the fungus.